Elevated compartmentalization of Na+ into vacuoles improves salt and cold stress tolerance in sweet potato (Ipomoea batatas). Issue 4 (8th November 2014) - Fan, Weijuan; Deng, Gaifang; Wang, Hongxia; Zhang, Hongxia; Zhang, Peng
<x xml:space="preserve">Abstract</x> Salinity and low temperature are the main limiting factors for sweet potato (Ipomoea batatas) growth and agricultural productivity. Various studies have shown that plant NHX‐type antiporter plays a crucial role in regulating plant tolerance to salt stress by intracellular Na+ compartmentalization. The Arabidopsis thaliana AtNHX1 gene that encodes a vacuolar Na+/H+ antiporter was introduced into the sweet potato cultivar Xushu‐22 by Agrobacterium‐mediated transformation to confer abiotic stress tolerance. Stable insertion of AtNHX1 into the sweet potato genome and its expression was confirmed by Southern blot and reverse transcription‐polymerase chain reaction (RT‐PCR). A remarkably higher Na+/H+ exchange activity of tonoplast membrane from transgenic sweet potato lines (NOE) in comparison with wild‐type (WT) plants confirmed the vacuolar antiporter function in mediating Na+/H+ exchange. Under salt stress, NOE plants accumulated higher Na+ and K+ levels in their tissues compared with WT plants, maintaining high K+/Na+ ratios. Consequently, NOE plants showed enhanced protection against cell damage due to the increased proline accumulation, preserved cell membrane integrity, enhanced reactive oxygen species (ROS) scavenging (e.g. increased superoxide dismutase activity), and reduced H2O2 and malondialdehyde (MDA) production. Moreover, the transgenic plants showed improved cold tolerance through multiple mechanisms of action, revealing the first molecular evidence for NHX1 function in cold response. The transgenic plants showed better biomass production and root yield under stressful conditions. These findings demonstrate that overexpressing AtNHX1 in sweet potato renders the crop tolerant to both salt and cold stresses, providing a greater capacity for the use of AtNHX1 in improving crop performance under combined abiotic stress conditions.